Data transmission strategy of P2P pattern live video media streaming system - SUN Zhi-xin1; CHEN Ya-dang1; REN Zhi-guang1 (Tongxin xuebao)
An algorithm optimization was made with improved simulated annealing algorithm aimed at data transmission strategy of streaming media system in P2P networks.According with global layout,a mathematic model have been estab-lished for data transmission strategy of streaming media system in P2P networks named VMDTSA-P2P,which com-pletely have considered the affection of both the out-bandwidth and the available time,and take them as the object func-tion for getting the optimum solution.It also optimized the solutions with improved simulated annealing algorithm.Compared with traditional data transmission strategies,this improved algorithm accelerates the speed of new nodes choose the data provider from its partner nodes when there are lots of users and insures the solution of the data provider is approximate the best.Thus,the play delay of the streaming media system is decreased and the quality of video playback is increased.By realizing it in a simulated P2P system,the accuracy and the efficiency were both verified in the simulation.